2014
DOI: 10.3310/phr02070
|View full text |Cite
|
Sign up to set email alerts
|

Putting Life in Years (PLINY): a randomised controlled trial and mixed-methods process evaluation of a telephone friendship intervention to improve mental well-being in independently living older people

Abstract: BackgroundSocial isolation in older adults is associated with morbidity. Evaluating interventions to promote social engagement is a research priority.MethodsA parallel-group randomised controlled trial was planned to evaluate whether telephone friendship (TF) improves the well-being of independently living older people. An internal pilot aimed to recruit 68 participants by 30 September 2012, with 80% retained at 6 months. Randomisation was web based and only analysts were blind to allocation. A service provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(53 citation statements)
references
References 90 publications
0
53
0
Order By: Relevance
“…However, some of those who did receive the intervention expressed disappointment at the manner in which the volunteers ended the group after the 12‐week intervention period (Hind et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, some of those who did receive the intervention expressed disappointment at the manner in which the volunteers ended the group after the 12‐week intervention period (Hind et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Semi‐structured interviews were conducted with all available volunteers upon study cessation and are reported elsewhere Hind et al . .…”
Section: Methodsmentioning
confidence: 99%
“…Psychological improvements were supported by trials with impact on self-esteem58 and caregiver burden,60–63 but effects on self-efficacy and mastery were not achieved 64 65…”
Section: Discussionmentioning
confidence: 99%
“…LM [2] Lifestyle Matters. PLINY [3] Putting Life IN Years. REPOSE [4] Relative Effectiveness of Pumps Over Structured Education.…”
Section: Included Trialsmentioning
confidence: 99%
“…A case-based approached was adopted to present the challenges of implementing group interventions in five RCTs [1][2][3][4][5] evaluating group interventions (Table 1) managed by Sheffield CTRU [45]-a UK Clinical Research Collaboration (UKCRC)-registered clinical trial unit managing phase III RCTs of a range of interventions across varied research areas. The CTRU has managed a number of evaluations of complex interventions, including five completed group intervention trials.…”
Section: Case Studiesmentioning
confidence: 99%